1994
DOI: 10.1177/42.7.8014475
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin B activity in human lung tumor cell lines: ultrastructural localization, pH sensitivity, and inhibitor status at the cellular level.

Abstract: We investigated the appearance and activity of the cysteine proteinase cathepsin B and its physiological inhibitors, stefii A and B, at the cellular level in human tumor cell lines HS-24, derived from a primary lung tumor (squamous cell), and SB-3, derived from a metastasis (lung adenocarcinoma). In addition to cathepsin B, these tumor cells also expressed the immunologically and hctionally related cathepsin L, but not cathepsin H. Stefin A was found in HS-24 but not in SB-3 cells; stefm B was found in both ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 13 publications
1
36
0
Order By: Relevance
“…Finally, metastasis of several malignancies is associated with increased production and/or secretion of cathepsin B (Sloane and Honn, 1984;Moin et al, 1989;Keppler et al, 1994), possibly promoting extracellular matrix degradation needed for tumor cell dissemination. Under these circumstances, various cathepsin B isoforms have been detected (Page et al, 1992), some of which were shown to be active at neutral pH (Buck et al, 1992;Spiess et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, metastasis of several malignancies is associated with increased production and/or secretion of cathepsin B (Sloane and Honn, 1984;Moin et al, 1989;Keppler et al, 1994), possibly promoting extracellular matrix degradation needed for tumor cell dissemination. Under these circumstances, various cathepsin B isoforms have been detected (Page et al, 1992), some of which were shown to be active at neutral pH (Buck et al, 1992;Spiess et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Among the cysteine proteinases, cathepsin B expression has been particularly well documented in a variety of tumor cell types (Friedrich et al, 1999;Heidtmann et al, 1997) including brain tumors (Demchik et al, 1999;Rempel et al, 1994). It has been suggested that cathepsin B can mediate dissemination of cancer cells by degrading ECM (Spiess et al, 1994) and/or activating other proteinases capable of degrading the matrix (Kobayashi et al, 1993). Buck et al (1992) have shown that cathepsin B can degrade the major components of basement membranes, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Cathepsin B levels are elevated in malignant tumors, particularly at the invasive edge of the tumor. The increased expression of cathepsin B mRNA has been reported in several human tumors including brain, colon, lung, prostate and esophageal adenocarcinoma (Spiess et al, 1994;Mikkelsen et al, 1995;Iacobuzio-Donahue et al, 1997;Hizel et al, 1998;Hughes et al, 1998). In addition, an increased abundance of cathepsin B transcripts and protein in tumor tissues correlates with clinical invasive features (Iacobuzio-Donahue et al, 1997;Hizel et al, 1998).…”
Section: Introductionmentioning
confidence: 97%